Puting beliung: Understanding Indonesia's small-scale tornadoes and the path forwardA literature review - Perdinan, Perdinan; Koesmaryono, Yonny; Hidayat, Rahmat; Permana, Donaldi Sukma; Kiki, Kiki (TDMRC, Universitas Syiah Kuala, 2025)
Puting beliung (PB), a tornado-like event in Indonesia, poses significant threats to communities and infrastructure, yet research on their characteristics and impacts remains limited. This study systematically reviews the progress of PB research in Indonesia through an analysis of 58 relevant studies, focusing on geographical distribution, characteristics, impacts, and mitigation efforts. Using Google Scholar as the primary search engine for scientific journal retrieval and implementing the PRISMA methodology for systematic literature review, this study ensures a comprehensive and structured analysis of existing research. Findings indicate that PB events predominantly occur in Java, with notably fewer documented cases in eastern Indonesia. These events are influenced by atmospheric conditions and spatiotemporal patterns, with psychological and structural impacts on affected communities. Existing mitigation strategies, including early warning systems, show promise but face challenges in public engagement and coordination, particularly in post-disaster recovery phases. The review highlights the need for integrating advanced technologies such as remote sensing and machine learning to improve prediction accuracy and develop a comprehensive PB event database. By synthesizing existing research, this study identifies and underscores the necessity for more extensive investigations, particularly under-research regions. Future research should prioritize improving forecasting models, expanding the geographical scope of studies, and enhancing disaster management strategies to minimize PB-related risks. Strengthening public awareness and response mechanisms is crucial to reducing vulnerabilities and improving resilience.